Real‐Time Cellular Imaging of Protein Poly(ADP‐ribos)ylation. Issue 37 (28th July 2016) - Buntz, Annette; Wallrodt, Sarah; Gwosch, Eva; Schmalz, Michael; Beneke, Sascha; Ferrando‐May, Elisa; Marx, Andreas; Zumbusch, Andreas
Abstract: Poly(ADP‐ribos)ylation (PARylation) is an important posttranslational protein modification, and is involved in major cellular processes such as gene regulation and DNA repair. Its dysregulation has been linked to several diseases, including cancer. Despite its importance, methods to observe PARylation dynamics within cells are rare. By following a chemical biology approach, we developed a fluorescent NAD + analogue that proved to be a competitive building block for protein PARylation in vitro and in cells. This allowed us to directly monitor the turnover of PAR in living cells at DNA damage sites after near‐infrared (NIR) microirradiation. Additionally, covalent and noncovalent interactions of selected target proteins with PAR chains were visualized in cells by using FLIM‐FRET microscopy. Our results open up new opportunities for the study of protein PARylation in real time and in live cells, and will thus contribute to a better understanding of its significance in a cellular context. Abstract : PARylation live : A fluorescent NAD + analogue was developed that enables the direct observation of poly(ADP‐ribose) (PAR) turnover in living cells in response to DNA damage induced by microirradiation. In combination with FLIM‐FRET microscopy, this analogue provides a powerful tool for the protein‐specific monitoring of both covalent and noncovalent interactions with the nucleotide‐based PAR biopolymer.